2017
DOI: 10.1002/esp.4260
|View full text |Cite
|
Sign up to set email alerts
|

Does the permeability of gravel river beds affect near‐bed hydrodynamics?

Abstract: The permeability of river beds is an important control on hyporheic flow and the movement of fine sediment and solutes into and out of the bed. However, relatively little is known about the effect of bed permeability on overlying near-bed flow dynamics, and thus on fluid advection at the sediment-water interface. This study provides the first quantification of this effect for water-worked gravel beds. Laboratory experiments in a recirculating flume revealed that flows over permeable beds exhibit fundamental di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 58 publications
(116 reference statements)
1
30
1
Order By: Relevance
“…The flow patterns over the permeable and non-permeable test section were compared based on velocity measurements obtained with Particle Image Velocimetry (PIV). Focusing on the near-bed region, Cooper et al [32] concluded that the flow resistance imposed by the non-porous surface was higher than that by the porous water-worked gravel-bed, which is contrary to the previous findings. Cooper et al [32] explained their findings from the analysis of the flow velocity data acquired at the roughness crest.…”
Section: Introductionmentioning
confidence: 73%
See 4 more Smart Citations
“…The flow patterns over the permeable and non-permeable test section were compared based on velocity measurements obtained with Particle Image Velocimetry (PIV). Focusing on the near-bed region, Cooper et al [32] concluded that the flow resistance imposed by the non-porous surface was higher than that by the porous water-worked gravel-bed, which is contrary to the previous findings. Cooper et al [32] explained their findings from the analysis of the flow velocity data acquired at the roughness crest.…”
Section: Introductionmentioning
confidence: 73%
“…Focusing on the near-bed region, Cooper et al [32] concluded that the flow resistance imposed by the non-porous surface was higher than that by the porous water-worked gravel-bed, which is contrary to the previous findings. Cooper et al [32] explained their findings from the analysis of the flow velocity data acquired at the roughness crest. They observed higher double-averaged velocities (velocities averaged in the time and space domain) over the gravel-bed than over the reproduced section and hypothesized that the higher efficiency in the momentum transfer and lower kinetic energy over the porous gravel-bed is a strong indicator that less energy was extracted from the mean flow.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations